Past changes in ocean circulation at intermediate water depth in the Atlantic Ocean from micropaleontological and geochemical study of marine sediment cores since the Last Glacial Maximum - Pourtout, Solène (HAL CCSD, 2023)
Intermediate water circulation is a key player in global ocean circulation and contributes to the variability of the Atlantic Meridional Overturning Circulation (AMOC) which plays a fundamental role in climate regulation. However, the ocean dynamics at intermediate depths since the Last Glacial Maximum (LGM) remains controversial and still needs to be constrained, in particular to better understand the relationships between the Atlantic Ocean and the Southern Ocean at the glacial-interglacial scale as well as during shorter climatic events that notably punctuated the Last Deglaciation (cold events of Heinrich Stadial 1, HS1 and Younger Dryas, YD). The objective of this thesis is to reconstruct the evolution of the circulation at intermediate water depth from the LGM from marine sediment cores taken from the Iberian margin (SU92-28, 997m) and north of the Porcupine bank (MD01-2461, 1153m). These sites are ideally located to reconstruct the variations in the contribution of intermediate water masses from the North and South of the Atlantic and the Mediterranean Sea. The combination of different micropaleontological and geochemical tracers (assemblages of benthic foraminifera, δ¹⁸O, δ¹³C, age difference Δ¹⁴C, εNd and elementary ratios) made it possible to reconstruct hydrological changes at intermediate water depth at high resolution temporal over the last 25ka. Our results show an exclusively well-ventilated Glacial North Atlantic (GNAIW) contribution, with no contribution from the Mediterranean Sea Water (MSW) during the LGM at both sites. During HS1 and YD, at the Iberian margin, an incursion of Antarctic Intermediate Water (AAIW), in association with MSW is recorded. However, the faunal assemblages from core MD01-2461 show the only presence of MSW at 1153m during HS1 and YD. In Bølling Allerød (BA) and in the Holocene, a mixing between the North, South and MSW components is recorded on the Iberian margin while only the North and MSW components are recorded on the Porcupine bank, reflecting the gradual restart ...